2022
DOI: 10.2147/ijgm.s349379
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Biomarkers Related to Regulatory T Cell Infiltration in Oral Squamous Cell Carcinoma Based on Integrated Bioinformatics Analysis

Abstract: Background: Oral squamous cell carcinoma (OSCC) is one of the most prevalent malignancies worldwide. More recently, the administration of immune checkpoint inhibitors has opened up more possibilities for cancer treatment. Methods: We utilized a weighted gene co-expression network and the single sample gene set enrichment analysis (ssGSEA) algorithm in the TCGA database and identified a module highly correlated with regulatory T cell (Treg) abundance in OSCC. Subsequently, we verified the results by tissue micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…Overexpression of LCK contributes to a large number of other diseases such as cancer, systemic lupus erythematosus and organ transplant rejection ( 43 ). It has been reported that knockdown of LCK significantly inhibits cell proliferation and cell invasion in Oral squamous cell carcinoma (OSCC) ( 44 ). Another report stated that inhibition or downregulation of LCK led to apoptosis in Chronic Lymphocytic Leukemia (CLL) cell lines ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of LCK contributes to a large number of other diseases such as cancer, systemic lupus erythematosus and organ transplant rejection ( 43 ). It has been reported that knockdown of LCK significantly inhibits cell proliferation and cell invasion in Oral squamous cell carcinoma (OSCC) ( 44 ). Another report stated that inhibition or downregulation of LCK led to apoptosis in Chronic Lymphocytic Leukemia (CLL) cell lines ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given the above key roles of TNFR2 in tumor cell survival, angiogenesis, and immune escape, targeting TNFR2 is becoming an important strategy for tumor therapy (Al‐hatamleh et al., 2020; Li et al., 2022; Segués et al., 2021). However, in the case of OSCCs, the expression and function of TNFR2 have been rarely studied (Wang et al., 2022), and whether TNF‐α promotes paracrine signaling in tumor cells for angiogenesis via TNFR2 remains unclear. In addition, sustained endothelial activation of Akt has been shown to induce the formation of abnormal blood vessels, and the Akt/mTOR pathway has been implicated in the regulation of angiogenesis (Karar & Maity, 2011).…”
Section: Introductionmentioning
confidence: 99%